Jejunal varices secondary to superior mesenteric vein thrombosis: an unusual cause of bleeding from the small intestine - Bejarano Rengifo, Janeth (2020)
Small bowel varices are usually associated with portal hypertension. Ectopic varices caused by isolated chronic superior mesenteric vein thrombosis are exceedingly rare. Gastrointestinal bleeding secondary to these represents a diagnostic challenge, given the low prevalence and clinical suspicion, and therapeutic dilemma due to the limited scientific evidence availableregarding treatment options. We present the case of a 56-year-old man with gastrointestinal bleeding from jejunal varices due to chronic superior mesenteric vein thrombosis, associated with thrombophilia; diagnosed by video capsule endoscopic (VCE) and computed tomography enterography (CTE), with no possibility of endoscopic or radiological management given the extensive involvement, who underwent successful surgery.